Association Between ABCG1/TCF7L2 and Type 2 Diabetes Mellitus: An Intervention Trial Based on a Case–Control Study - Yinxia Su; Bo Shang; Xiaoyuan Hu; Zhihao Zhang; Li Wang; Kun Luo; Hua Yao; Xiangtao Liu; Yaoqin Lu; Sheng Jiang (Journal of Diabetes Research)
Conclusions: The interaction of the rs7901695 site of the TCF7L2 gene and the cg06500161 site of the ABCG1 gene with environmental factors may increase the risk of T2DM in Uyghurs. The interaction between the cg06500161 site of the ABCG1 gene and environmental factors on T2DM varied with the intervention. The cg06500161 site of ABCG1 may serve as a biomarker to evaluate the effect of T2DM interventions.